MULTIPLE-PERSPECTIVE ANALYSIS ON THE GEOLOGICAL DISTRIBUTION OF CHRISTIANS IN CHINA - Gai, Rong Hua; Gao, Jun Hui (PEOPLE: International Journal of Social Sciences, 2016)
This article uses GIS technology to obtain the geographical distribution of Christians in China based on the data on religions in each Chinese province collected by CFPS in 2012. After processing the data, we get the geographical distribution of proportion of Christian population in all religious people in each Chinese province. Furthermore, this article tries to explore reasons that can explain such distribution from multiple dimensions, including history, religious ecology, and religious studies. First of all, we find out that the number of Christians has made Christianity the second largest religion in China, while the first one is Buddhism; however, Christianity is developing much faster than Buddhism. In addition, this article finds out an astonishing phenomenon: the population of Christians is almost the same as that of Buddhism in Henan, the birthplace of Shaolin (a branch of Buddhism).